Synthetic coordination chemistry : principles and practice - Davies, Julian A.; World Scientific (Firm) (Singapore ; River Edge, N.J. : World Scientific Pub. Co., 1996)
Although coordination chemistry naturally centers on the synthesis of coordination compounds, the synthesis of these materials is typically not an end in itself. Coordination compounds are utilized in all branches of chemistry; from theoretical modeling to industrial and consumer products. While a large amount of information is available on coordination chemistry in general and synthetic methods in particular, no comprehensive work has been presented on the preparation of coordination compounds with an emphasis on synthetic strategies rather than on detailed descriptions of specific syntheses. The goal of this book is to provide an approach to coordination chemistry that is based upon preparative strategies. The main aim of the authors is to present a systematic classification of synthetic reactions rather than an encyclopedic listing of experimental results. Hence, the coverage is more selective than exhaustive. Despite this, the book provides access to the original literature with ca. 2000 references. The edition is well-illustrated and contains almost 250 schemes, figures and illustrations of crystal structures of selected complexes.
ch. 9. Reductants in preparative coordination chemistry. 9.1. Reduction by metals and amalgams. 9.2. Reduction by organic radical-anions and anions. 9.3. Carbon monoxide and other carbon-containing reductants. 9.4. Sulfur-containing reductants. 9.5. Low oxidation state metal ions. 9.6. Tertiary phosphines and phosphites. 9.7. Other reductants -- ch. 10. Boron and aluminium hydrides in preparative coordination chemistry. 10.1. Applications of boron and aluminum hydrides in the synthesis of metal hydrides. 10.2. Reduction without formation of M-H bonds. 10.3. Application of hydrides as reductants for coordinated carbonyl ligands. 10.4. Reactions of boron and aluminum hydrides with unsaturated hydrocarbyls and related ligands. 10.5. Reactions of boron and aluminum hydrides with other coordinated ligands -- ch. 11. Molecular rearrangements of coordination compounds. 11.1. Rearrangements involving changes in metal-ligand binding sites. 11.2. Rearrangements involving changes in coordination polyhedra. 11.3. Rearrangement of coordinated ligands on a metal framework. 11.4. Rearrangement of [symbol]-olefin complexes to [symbol]-organometallics. 11.5. Rearrangement of acyl ligands to alkyl and carbonyl ligands. 11.6. Interligand oxygen transfer. 11.7. Conversion of phosphite complexes to phosphonate complexes -- ch. 12. Solid state thermal synthesis of coordination compounds. 12.1. The Anderson rearrangement. 12.2. Dehydration and deaquation. 12.3. Syntheses involving abstraction of amine and other neutral ligands. 12.4. Solid state thermal polymerization. 12.5. Syntheses that involve deprotonation of a coordinated ligand followed by ring-closure. 12.6 Thermal deprotonation of coordinated ammine ligands. 12.7. Solid state cyclometallation. 12.8. Thermal decarboxylation and disproportionation. 12.9. Solid state thermal oxidation of tertiary phosphines. 12.10. Solid state geometric isomerization.
Includes bibliographical references and index.
Electronic reproduction.
Keywords: Coordination compounds -- Synthesis; Electronic books